2006
DOI: 10.5713/ajas.2006.1716
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Osmolality of Complete Semen Extender on Motion Characteristics of Frozen-thawed Ram Spermatozoa

Abstract: The present study was conducted to observe the effect of osmolality of glycerolated TEST-yolk glycerol extenders on post-thawing sperm kinematics of ram spermatozoa of the native Malpura breed maintained in a semi-arid tropical environment. Good quality semen obtained from adult rams was pooled, split and diluted to 1,000 million spermatozoa per ml in complete TEST-yolkglycerol extenders of 900, 1,200, 1,500 and 1,800 mOsm/kg osmolality. Diluted semen samples were loaded in 0.25 ml straws and cooled down to -1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 31 publications
2
7
0
Order By: Relevance
“…(Thundathil et al, 2000) and buffalo (Sengupta and Bhela, 1988) but bull fertility hardly affected if abnormal spermatozoa do not exceed 15 to 20% (Pant et al, 2002). In the present study the increase of abnormality (percent) is mainly in the tail which suggests that osmolality change in the media may be responsible for this increase as suggested by Joshi et al (2006).…”
Section: Sperm Abnormalitysupporting
confidence: 66%
“…(Thundathil et al, 2000) and buffalo (Sengupta and Bhela, 1988) but bull fertility hardly affected if abnormal spermatozoa do not exceed 15 to 20% (Pant et al, 2002). In the present study the increase of abnormality (percent) is mainly in the tail which suggests that osmolality change in the media may be responsible for this increase as suggested by Joshi et al (2006).…”
Section: Sperm Abnormalitysupporting
confidence: 66%
“…In agreement with our finding, Abdelhakeam et al (1991) reported that although maximum survival of ram spermatozoa before freezing was obtained with an isotonic extender, a hypertonic extender gave the highest post-thaw motility. Joshi et al (2006) found out that ram spermatozoa could tolerate a wide osmolality range for dilution. Also, these results agree with Fiser and Langford (1980) and Fiser et al (1982) who reported that hypertonic diluents are superior to isotonic diluents.…”
Section: Discussionmentioning
confidence: 99%
“…We have no explanation for the observation that when comparing fresh and frozen/thawed semen from insulated and control rams, the percentages of MOT, PROG and RAP sperm fell more following freezing and thawing than ALH, VAP, VCL or VSL, when these changes were expressed as percentages of the prefreezing values, except to suggest that this treatment might http://www.asiaandro.com; aja@sibs.ac.cn affect those sperm with good motility less than those with poor motility, causing the latter to become completely immotile, therefore increasing the average velocities that are calculated only on motile sperm. Apart from a brief report [12] of reductions in percent MOT and RAP sperm and a decrease in VCL, VAP, VSL and ALH following freezing and thawing of ram semen, there seems to be little information on the quantitative changes in motility characteristics resulting from freezing and thawing of ram semen with which to compare the results of the present study.…”
Section: Discussionmentioning
confidence: 75%
“…By reducing the duration of the scrotal insulation, it was also hoped that a threshold effect would be produced, which might also reveal if there was much variation in the response of the testes of individual rams to heat stress. As additional ways of reducing sperm motility, we have used freezing or liquid storage of the semen, as both these procedures have been reported to cause changes in the motility characteristics of ram sperm [11,12].…”
Section: Introductionmentioning
confidence: 99%